PENGEMBANGAN E-MODUL PEMBELAJARAN BERBASIS FLIPBOOK PADA KOMPETENSI DASAR MENERAPKAN TEKNIK KERJA ASEPTIS DI SMKN 1 KUNINGAN - Maudina Nuraisya Rahmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The aim of this research was to determine the feasibility of a flipbook-based e-module on the Basic Competence of Applying Aseptic Work Techniques and determine the learning outcomes of students after using a flipbook-based e-module on the Basic Competence of Applying Aseptic Work Techniques at SMKN 1 Kuningan. The development of this flipbook-based e-module uses the ADDIE development model. The sampling technique used in this research is purposive sampling. The research design used at the implementation stage was One group pre-test post-test. Based on the results of the pre-test and post-test, it was found that there was an increase in learning outcomes from the